Bioinformatic and Experimental Analysis of T Cell Immune Reactivity to SARS-CoV-2 and its Variants - Tarke, Alison; Grifoni, Alba; Sette, Alessandro (Frontiers in Bioinformatics, 2022)
Definition of the T cells responses to SARS-CoV-2 and associated variants is critical to understanding the complexity of adaptive immunity against SARS-CoV-2 infection. Several groups have investigated the T cells responses by both experimental and bioinformatical approaches. Here we summarize recent findings on CD4 and CD8 T cell responses to SARS-CoV-2 with particular emphasis on emerging variants of concern, consolidating the results on the impact of SARS-CoV-2 variants on T cell responses by performing an additional metanalysis emphasizing the lower impact of variant mutations in dominant T cell epitopes. The consensus is that the majority of T cell responses are conserved across all current SARS-CoV-2 variants, including Delta and Omicron. Thus, even in concomitance with reduced antibody and B cell responses, T cells can still provide a second line of antiviral immunity.